2013
DOI: 10.1002/jsfa.6031
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between polyphenol content and anti‐influenza viral effects of berries

Abstract: Antiviral effects were found to differ markedly between berry species. Rabbiteye varieties tended to have higher antiviral effects than Northern, Southern and Half Highbush blueberry varieties. We also found that Natsuhaze, which has recently been harvested in Japan as a potential functional food, had an antiviral effect comparable to that of bilberry, cranberry and blackcurrant. There was a positive relationship between antiviral activity and polyphenol content, indicating the possibility that polyphenol is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…The cytotoxicity of each compound (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) was evaluated by cell proliferation assay. Flavones (8)(9), flavonols (11)(12)(13) and 16 exhibited relatively high cytotoxic effects when compared with other flavonoids, although their selectivity index (CC 50 /IC 50 ) was larger than 500. Interestingly, they all have planar pai-conjugated systems.…”
Section: Cytotoxicities Of Natural Flavonoids and Gallic Acid Derivatmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxicity of each compound (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) was evaluated by cell proliferation assay. Flavones (8)(9), flavonols (11)(12)(13) and 16 exhibited relatively high cytotoxic effects when compared with other flavonoids, although their selectivity index (CC 50 /IC 50 ) was larger than 500. Interestingly, they all have planar pai-conjugated systems.…”
Section: Cytotoxicities Of Natural Flavonoids and Gallic Acid Derivatmentioning
confidence: 99%
“…We reported that epigallocatechin gallate, a major green tea catechin, and its fatty acid derivatives directly inhibit various types of influenza virus including neuraminidase inhibitor resistant viruses [6,7]. Natural flavonoids in pomegranate [8], berries [9], and plant seeds [10] have also been reported to be effective for inhibition of virus infection. However, little is known about the antiviral activity of coffee extracts [10,11], despite its status as the most-consumed drink in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cranberry extracts may also represent a source of potential compounds that would prevent viral attachment to target cells as well. Indeed, antiviral activities of cranberry extracts have been reported against Reovirus ( Lipson et al, 2007 ), Enterovirus ( Su et al, 2010 ), and even against IV ( Weiss et al, 2005 ; Oiknine-Djian et al, 2012 ; Sekizawa et al, 2013 ). However, a lack of mechanistic studies and the standardization of productive processes to maintain comparable bioactive components concentrations, have limited the development of cranberry products as antivirals against IV infections.…”
Section: Introductionmentioning
confidence: 99%
“…bioregulatory functions involved in the maintenance and improvement of health), which are attributed to the presence of various bioactive components. For example, flavonoids, a category of polyphenols that includes catechins from green tea, have been reported to have anti‐influenza virus effects …”
Section: Introductionmentioning
confidence: 99%